Émanciper et conformer : les tensions de la socialisation civique à l'école primaire - Géraldine Bozec (Nantes Université, 2014)
The construction of pupils' political autonomy, which relates to the role of citizenship education of French public education since the Third Republic, has been a controversial issue for three decades: the citizenship rights that are to be granted to children inside schools themselves have been more and more emphasized. However, on the basis of a qualitative study in primary schools, it can be noted that civic autonomy is not understood and implemented in the same way from one classroom to another, depending upon teachers' ideological profiles and social contexts of teaching. Beyond these variations, civic autonomy is above all thought at school as the emancipation of children from their family - and from some families in particular - and their adhesion to the rules and values that are those of the school institution and/or of the teacher. This process leads to differentiated judgments on children, according to the features of their family socialization, which can be more or less congruent, in terms of political beliefs and school behaviours, with what is valued by teachers. Political autonomy at school also emphasizes the individual citizen - instead of the actor who belongs to different communities, whatever they are - because it is deeply connected to the autonomy of thought and to intellectual independence.